2016
DOI: 10.3109/07357907.2016.1139716
|View full text |Cite
|
Sign up to set email alerts
|

Does the Presence of Endometriosis Affect Prognosis of Ovarian Cancer?

Abstract: Objective To characterize ovarian cancers associated with endometriosis and to evaluate the prognostic impact of endometriosis. Methods Ovarian cancer cases from a single institution diagnosed between 2000 and 2013 were examined and specimens reviewed by two pathologists for the presence of endometriosis. Ovarian cancer cases with and without endometriosis were compared to determine the clinical factors associated with endometriosis and the prognostic significance of endometriosis. Two-sample T-tests, Chi-sq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…While large amounts of genomic data have been generated based on histotype, there is limited information regarding the molecular contribution of the endometriotic tumor microenvironment on OEA. While this subtle pathologic diagnosis is often overlooked in research studies, the improvement of outcomes of women with endometriosis at time of ovarian cancer staging is not . Therefore, the molecular contributions of the endometriotic tumor microenvironment may affect the overall tumor biology.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While large amounts of genomic data have been generated based on histotype, there is limited information regarding the molecular contribution of the endometriotic tumor microenvironment on OEA. While this subtle pathologic diagnosis is often overlooked in research studies, the improvement of outcomes of women with endometriosis at time of ovarian cancer staging is not . Therefore, the molecular contributions of the endometriotic tumor microenvironment may affect the overall tumor biology.…”
Section: Discussionmentioning
confidence: 99%
“…While this subtle pathologic diagnosis is often overlooked in research studies, the improvement of outcomes of women with endometriosis at time of ovarian cancer staging is not. [7][8][9] Therefore, the molecular contributions of the endometriotic tumor microenvironment may affect the overall tumor biology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 11 A study that included 139 patients with epithelial ovarian cancer (49 with endometriosis and 90 without endometriosis) showed that patients with EAOC were younger, and more likely confined to the pelvis (54% vs. 9%) and at lower grade (51% vs. 29%) at diagnosis compared with patients with non-EAOC. 31 Current reports on the survival outcome of EAOC were basically comparing the survival differences between EAOC and non-EAOC patients. In a metaanalysis on 20 case–control and 15 cohort studies that included 444,255 patients reported that there were no differences in progression free survival (PFS) (HR, 1.023), but a slightly better overall survival (OS) by crude analyses (HR, 0.778) in EAOC than non-EAOC.…”
Section: Survival Outcome Of Eaocmentioning
confidence: 99%